HEV-associated dendritic cells are observed in metastatic tumor-draining lymph nodes of cutaneous melanoma patients with longer distant metastasis-free survival after adjuvant immunotherapy - Bravo, Alicia Inés (2023)
Introduction: Tissue biomarkers that aid in identifying cutaneous melanoma (CM) patients who will benefit from adjuvant immunotherapy are of crucial interest. Metastatic tumor-draining lymph nodes (mTDLN) are the first encounter site between the metastatic CM cells and an organized immune structure. Therefore, their study may reveal mechanisms that could influence patients´ outcomes. Methods: Twenty-nine stage-III CM patients enrolled in clinical trials to study the vaccine VACCIMEL were included in this retrospective study. After radical mTDLN dissection, patients were treated with VACCIMEL (n=22) or IFNα-2b (n=6), unless rapid progression (n=1). Distant Metastasis-Free Survival (DMFS) was selected as an end-point. Two cohorts of patients were selected: one with a good outcome (GO) (n=17; median DMFS 130.0 months), and another with a bad outcome (BO) (n=12; median DMFS 8.5 months). We analyzed by immunohistochemistry and immunofluorescence the expression of relevant biomarkers to tumor-cell biology and immune cells and structures in mTDLN, both in the tumor and peritumoral areas. Results: In BO patients, highly replicating Ki-67+ tumor cells, low tumor HLA-I expression and abundant FoxP3+ lymphocytes were found (p=0.037; p=0.056 and p=0.021). In GO patients, the most favorable biomarkers for prolonged DMFS were the abundance of peri- and intra-tumoral CD11c+ cells (p=0.0002 and p=0.001), peri-tumoral DC-LAMP+ dendritic cells (DCs) (p=0.001), and PNAd+ High Endothelial Venules (HEVs) (p=0.004). Most strikingly, we describe in GO patients a peculiar, heterogeneous structure that we named FAPS (Favoring Antigen-Presenting Structure), a triad composed of DC, HEV and CD62L+ naïve lymphocytes, whose postulated role would be to favor tumor antigen (Ag) priming of incoming naïve lymphocytes. We also found in GO patients a preferential tumor infiltration of CD8+ and CD20+ lymphocytes (p=0.004 and p=0.027), as well as peritumoral CD20+ aggregates, with no CD21+ follicular dendritic cells detected (p=0.023). Heterogeneous infiltration with CD64+CD68-CD163-, CD64+CD68+CD163- and CD64+CD68+CD163+ macrophages were observed in both cohorts. Discussion: The analysis of mTDLN in GO and BO patients revealed marked differences. This work highlights the importance of analyzing resected mTDLN from CM patients and suggests a correlation between tumor and immune characteristics that may be associated with a spontaneous or vaccine-induced long DMFS. These results should be confirmed in prospective studies.